Partisipasi Kelompok Wanita Tani Sedana Amerta Sari pada Program Pekarangan Pangan Lestari (Studi Kasus Desa Angantaka, Kecamatan Abiansemal, Kabupaten Badung) - SARI, NI KADEK AYU PUTRI DITA; PITANA, I GDE; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Participation of Members of Sedana Amerta Sari Women Farmer Group in Sustainable Food Yard Program: Case Study of Angantaka Village, Abiansemal District, Badung Regency.  The Sustainable Food Yard Program has the potential to achieve food self-sufficiency. The development of the program requires active participation of farmers. This study aims to analyze the level of participation, describe the forms of participation and the obstacles faced by the Sedana Amerta Sari Women Farmer Group (KWT). The research was conducted in the village of Angantaka and involved 30 respondents who are members of KWT. Data collection was carried out using a combination of in-depth interview techniques, observation and documentation to describe the forms and constraints of participation. Survey was carried out to determine the level of KWT participation. The data were then analyzed using descriptive qualitative methods. The result shows that the participation of KWT members is at a moderate level in all indicators of research variables such as participation in decision making, program implementation, program monitoring and utilization of results (56.16%). In terms of technical aspect, participation constraints faced by KWT include the lack of management time, the presence of pests and diseases, the unavailability of electricity and clean water on the demonstration plot. Economically, KWT members are facing capital constraints for the maintenance and development of agrotourism. Finally, the KWT lacks solidarity and internal group communication in terms of social aspects.